THE CORRELATION BETWEEN ENERGY, CARBOHYDRATE, FAT AND PROTEIN CONSUMPTION LEVEL WITH DEMENSIA IN ELDERLY - Bekti Krisdyana; Diffah Hanim; Sugiarto Sugiarto (Universitas Airlangga, 2021)
Increasing number of elderly population due to infl uence of increased life expectancy, has an impact on increasing various health problems that occur due to aging process, one of which is dementia. Dementia is infl uenced by various factors, one of which is the level of nutrient consumption. The purpose of this study was to examine the relationship between level of energy consumption, carbohydrate, fat and protein with dementia in elderly. The population was elderly (> 60 y.o) in Tulungagung Regency. This study was cross sectional study with sampling techniques were used cluster random sampling. Samples in this study was 165 person. Variable analysed used chi square test. There were relationship between age, energy and protein consumption level with dementia in elderly (p <0.05). Elderly who have dementia majority are over 70 years old (60.5%). The majority of elderly with dementia have energy and protein consumption level in low category, that is 48.7% and 55.3%, respectively. The conclusion is that there were correlation between age, level of energy and protein consumption with the incidence of dementia in elderly.